Of men and monsters : Jeffrey Dahmer and the construction of the serial killer - Tithecott, Richard (Book collections on Project MUSE., 1997)
"Examines the serial killer as an American cultural icon, one that both attracts and repels. Richard Tithecott suggests that the stories we tell and the images we conjure of serial killers--real and fictional--reveal as much about mainstream culture and its values, desires, and anxieties as they do about the killers themselves"--Page 4 of cover